Molecular docking and in-silico predictive analysis of potential herb-drug interactions between Momordica charantia and Empagliflozin - Karur Venkatesan Uma, Jacob Vineth Martin, Gunasekaran Sutheeswaran, Raman Rajeshkumar, Sivasankaran Ponnusankar (Journal of Applied Pharmaceutical Science, 2023)
The most prominent sequel of multidrug regimens in type 2 diabetes mellitus patients include polypharmacy, non-compliance with medications, and increased financial burden. An extensive study on beneficial herb-drug interactions is required to overcome the above concern. Molecular docking and in-silico approaches can be employed to better understand potential herb-drug interactions. These interactions are presumed to occur at the level of pharmacokinetics. Herbal phytoconstituents can either accelerate or slow down the absorption, distribution, metabolism, excretion, and efficacy of a drug. If these interactions are proven to be beneficial, meaning, if they can accelerate the absorption and distribution of the drug and decelerate the metabolism and elimination of the drug, the efficacy of the drug can be increased. As a result, dose escalation, frequency of drug administration, and the addition of anti-diabetic medications to current treatment can be prolonged. This study attempted to computationally analyze the phytoconstituents of Momordica charantia for drug likeliness and their binding affinity to specific proteins involved in the pharmacokinetics of Empagliflozin. Additionally, the nature of chemical bonding and binding locations of phytoconstituents and Empagliflozin were studied to understand potential interactions. The findings showed that M. charantia and Empagliflozin did not elicit any favorable herb-drug interactions. This is attributed to the non-availability of sophisticated software that can determine the function of the amino-acid binding site. This study necessitates the development of advanced software to determine the function of the amino acid binding site in order to clearly comment on the herb-drug interaction outcome. Also, molecular dynamics and clinical pharmacokinetic investigations with the presented data are encouraged to confirm the findings.